Analysis of the strategic aims and objectives for Information and Communication Technology Implementation in the Lithuanian Education - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2008)
The paper deals with the survey made on the Strategy for Information and Communication Technology Implementation in Education for 2005–2007. Attention is paid to study the implementation of aims and objectives of the Strategy. Conclusions and some suggestions are presented at the end of the paper.